The Accuracy of the Online-Based Independent Study Method in Developing University Students' Entrepreneurship Skills - Badrus; Zakariyah; Sulthon, Muhammad (Tafkir: Interdisciplinary Journal of Islamic Education, 2024)
This study aims to analyze the impact of online-based independent learning methods on developing entrepreneurial skills among students at Private Universities in Kediri. The research focuses on 1) the types of entrepreneurial skills that students are keen on enhancing, 2) the strategies employed by tutors/lecturers to help students strengthen their entrepreneurial skills through online independent study, and 3) the effectiveness of online independent study methods on students' entrepreneurial skills with the guidance of lecturers. The study utilizes a research and development (R&D) approach. The research sample comprises 1) two classes of students from the Islamic Broadcasting Communication Study Program at the Faculty of Da'wah, UIT Lirboyo Kediri, and 2) two classes of students from the Management and Economics Study Program at UNP Kediri. The findings reveal that online-based independent study significantly influences the development of students' entrepreneurial skills. The entrepreneurial skills of interest include online stores, resellers, drop-shippers, and affiliate marketers. The tutor's strategy for fostering students' entrepreneurial skills involves generating new ideas, conducting idea feasibility tests, drafting business proposals, developing business products, creating online advertisements, practicing sales techniques in the field, and preparing sales reports. This tutoring approach contributes to the cultivation of innovative entrepreneurial skills that yield positive outcomes for students.